Cognitive decline and dementia in women after menopause: Prevention strategies. (February 2023) - Stefanowski, Bogdan; Kucharski, Marek; Szeliga, Anna; Snopek, Milena; Kostrzak, Anna; Smolarczyk, Roman; Maciejewska-Jeske, Marzena; Duszewska, Anna; Niwczyk, Olga; Drozd, Slawomir; Englert-Golon, Monika; Smolarczyk, Katarzyna; et al.
Highlights: Cognitive decline is one of the biggest challenges for public health. The menopausal transition is associated with cognitive changes which are mild and usually do not affect normal functioning. Menopausal symptoms can aggravate cognitive changes during the menopausal transition. Menopausal hormone therapy appears to have no deleterious effects on cognition. Addressing modifiable risk factors, such as cardiovascular risk factors, diabetes and lifestyle, can have a significant protective effect against cognitive decline and dementia. Abstract: Worldwide, cognitive decline and dementia are becoming one of the biggest challenges for public health. The decline in cognition and the development of dementia may be caused by predisposing or trigger factors. There is no consensus over whether the drop in estrogen levels after menopause is a risk factor for cognitive decline and dementia. This article discusses the prevention of cognitive decline and dementia in women after menopause, both primary prevention (essentially pharmacological intervention) and secondary prevention (chiefly diet and weight reduction). Further study is required to clarify whether menopausal hormone therapy (MHT) has a role in dementia.